Handwashing and antiseptic-containing soaps in hospital. Issue 7 (July 1979) - Jarvis, J. D.; Wynne, C. D.; Enwright, L.; Williams, J. D.
Abstract : Two aspects of handwashing in hospital were considered. A study was carried out to examine the contamination of bar soap and containers, and the use of antiseptic soaps in reducing the resident flora of the skin. Swabs were collected from soap dishes on six wards and from a bacteriology laboratory on four consecutive days. The unmedicated bar soap was replaced by bar soap containing 2·5% povidone-iodine, and further swabs were collected over a period of seven days. Ninety-two isolates from 48 samples were obtained when unmedicated bar soap was used, and nine isolates from 42 samples when povidone-iodine (Betadine) soap was substituted. The number of organisms recovered when povidone-iodine soap was used was much reduced, and Pseudomonas spp were recovered in low numbers on only one occasion. Six laboratory workers took part in a study to compare bar soap with other agents—povidone-iodine soap, povidone-iodine surgical scrub, povidone-iodine alcoholic solution, chlorhexidine surgical scrub, and alcoholic chlorhexidine. Samples were collected after standard washes and after surgical gloves had been worn for 90 minutes. The effect of multiple washes was assessed by samples collected after six washes with the agent under study (three per day) followed by 90 minutes wearing surgical gloves. The average percentage reduction in normal flora obtained indicated that alcoholic chlorhexidine was superior to the other agents.